Assessing Elias on Marx in a neoliberal age - Loyal, Steven (Política y Sociedad, 2013)
This paper assesses Elias’s recently published critique of Marx written in the 1960swithin the contemporary context of neo-liberalism. Based on a chapter written by Elias and intended for publication in What is Sociology? (1978) it argues that although Elias’s makes some acute and penetrating points in his assessment of Marx, on occasion he caricatures Marx’s arguments, and at other times recapitulates common erroneous criticisms. It argues that Elias’s position is actually closer to Marx than his misjudged criticisms suggest, and that both writers, despite their differences, have a particular relevance in the current neo-liberalism context characterised simultaneously by increasing global interdependencies and a ‘de-civilising’ spurt.